SILCC-Zoom: polarization and depolarization in molecular clouds - Seifried, Daniel; Reißl, Stefan (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We present synthetic dust polarization maps of 3D magneto-hydrodynamical simulations of molecular clouds before the onset of stellar feedback. The cl